Phytochemicals for improving aspects of cognitive function and psychological state potentially relevant to sports performance - Kennedy, D. O. (Sports Medicine, 2019)
Subjective alertness and optimal cognitive function, including in terms of attention, spatial/working memory and executive function, are intrinsic to peak performance in many sports. Consumption of a number of plant-derived `secondary metabolite` phytochemicals can modulate these psychological parameters, although there is a paucity of evidence collected in a sporting context. The structural groups into which these phytochemicals fall—phenolics, terpenes and alkaloids—vary in terms of the ecological roles they play for the plant, their toxicity and the extent to which they exert direct effects on brain function. The phenolics, including polyphenols, play protective roles in the plant, and represent a natural, benign component of the human diet. Increased consumption has been shown to improve cardiovascular function and is associated with long-term brain health. However, whilst short-term supplementation with polyphenols has been shown to consistently modulate cerebral blood-flow parameters, evidence of direct effects on cognitive function and alertness/arousal is currently comparatively weak. Terpenes play both attractant and deterrent roles in the plant, and typically occur less frequently in the diet. Single doses of volatile monoterpenes derived from edible herbs such as sage (Salvia officinalis/lavandulaefolia) and peppermint (Mentha piperita), diterpene-rich Ginkgo biloba extracts and triterpene-containing extracts from plants such as ginseng (Panax ginseng/quinquefolius) and Bacopa monnieri have all been shown to enhance relevant aspects of cognitive function and alertness. The alkaloids play toxic defensive roles in the plant, including via interference with herbivore brain function. Whilst most alkaloids are inappropriate in a sporting context due to toxicity and legal status, evidence suggests that single doses of nicotine and caffeine may be able to enhance relevant aspects of cognitive function and/or alertness. However, their benefits may be confounded by habituation and withdrawal effects in the longer term. The efficacy of volatile terpenes, triterpene-rich extracts and products combining low doses of caffeine with other phytochemicals deserves more research attention.